DESAIN KONSEP TENTANG KONTEN LOKAL PADA TELEVISI LOKAL UNTUK MENGEMBANGKAN WISATA KULINER KOTA MALANG - Lian Agustina Setiyaningsih (Universitas Merdeka Malang, 2016)
Abstract Television is a mainstream media that is able to survive amid the crush of media on line. Television developments occur until in the area, giving rise to local television. Indonesian Broadcasting Commission (KPI) has set up procedures local television aired on the Broadcasting Law No. 32/2012 and P3 SPS. Where local television has a role to develop the potential of the region. This study focused on the potential and promotional messages of Culture and Tourism (Dikbudpar) Malang. It also dug local television perspective in understanding the local content, which will be the two concepts will be used as a reference for designing the concept of local content on local television to develop culinary wosata Malamg. The method in this study is qualitative. To get the data researchers are working with informants from Dikbudpar Malang and local television in Malang. The data is then analyzed using interactive model of Miles and Huberman and domain analysis Spradley. This study aims to provide inputs to the government of Malang and local television media on the design concept of local content that can be used to develop culinary tourism Malang.DOI : https://doi.org/10.26905/nomosleca.v2i2.1198